Phytochemical and Antimicrobial Screening of Ethanol Extracts of Zingiber officinale, Allium sativum and Syzygium aromaticum against Some Food Associated Bacteria and Fungi - Aliyu, M.S.; Tijjani, M.B.; M.H.I. Doko; Garba, I.; Ajimego A.B.; Hanwa, U.A.; Ibrahim, M.M. (UMYU Journal of Microbiology Research)
The in vitro antimicrobial activities of ethanol extracts of ginger (Zingiber officinale), garlic (Allium sativum) and clove (Syzygium aromaticum) were evaluated against some bacteria (Staphylococcus aureus and Escherichia coli) and moulds (Aspergillus niger and Rhizopus stolonifer) isolated from food samples by agar well diffusion method and poisoned food technique respectively. The phytochemical screening revealed that the three extracts contained carbohydrates, flavonoids and triterpenes in addition to other bioactive components such as glycosides, saponins, steroids, tannins and alkaloids which varied among the extracts, however, anthraquinones are absent in all the extracts. The extracts showed inhibitory effects against the test organisms with zones of inhibition ranging from 10mm to 23mm at concentration range of 62.5 to 500mg/ml. The minimum inhibitory concentration (MIC) value of clove was 3.90mg/ml, ginger 62.5mg/ml and garlic 125mg/ml on both bacteria. The minimum bactericidal concentration (MBC) values were recorded for cloves at 15.62mg/ml while garlic and ginger had no MBC values. Percentage mycelial growth inhibitions ranging from 2.5% to 100% were recorded against the test fungi. Based on these findings, it may be suggested that these plant materials may be used as natural antimicrobial additives to improve the quality and shelf-life of foods.